Double electrical layer in the cathode spot - Gretchikhin, Leonid I.; Latushkina, Svetlana D.; Kamarouskaya, Viktoryia M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper describes a new phenomenon of the generation of the double electrical layer above the cathode spot surface. The neutralization of this layer leads to the reverse current of free electrons, generated due to negative ions ionization. The negatively charged flame of the cathode spot periodically ignites and attenuates, so the duration of the cathode spot existence is defined by this oscillating process. The reverse motion of the cathode spot in the longitudinal magnetic field takes place owing to the generation of the reverse high-power neutralization current of the double electrical layer by the electrons appearing during the negative ions ionization in the cathode flame.
Keywords: electric discharge; cathode spot; cathode flame; negative ions; double electrical layer